Exploring ageism in nursing students without grandparental co-residence: A photovoice study - Jiu Kim; Junggeun Ahn; Youngeun Park; Jangmi Baek (Journal of Korean Gerontological Nursing, 2026)
Purpose: This study aimed to explore the perceptions of older adults and the factors influencing ageism among nursing students without co-residential experience with grandparents. Methods: A qualitative approach using the photovoice method was employed. Participants were recruited through online communities of two universities. The final sample consisted of nine nursing students from these universities. Data were collected across five sessions, including orientation, three group discussions with photovoice activities, and individual interviews. Participants captured photographs reflecting their perceptions of older adults, provided descriptions, and engaged in group discussions that were guided in part by the principles of the SHOWeD technique. Data were analyzed using photovoice procedures and thematic analysis, following a process of selecting, contextualizing, and categorizing data to generate themes and subthemes. Results: Analysis of 72 photographs and associated narratives yielded three main themes: (1) “Confusion and rigidity revealed within a changing society,” (2) “A sense of distance formed through experiences of norm-breaking and social isolation,” (3) “Ambivalent perceptions shaped by everyday, welfare, and cultural experiences.” Participants demonstrated complex perceptions of older adults, reflecting both negative stereotypes and recognition of their engagement in cultural activities. Conclusion: Nursing students’ perceptions of older adults reflected ambivalent attitudes, with negative stereotypes coexisting with positive views. These findings suggest that limited intergenerational contact and media representations of older adults may be associated with ageist perceptions, highlighting the potential value of educational and intergenerational approaches to addressing ageism.